Creative Behavior as a Function of Task Environment: Impact of Objectives, Procedures, and Controls - Cummings, L. L.; Hinton, Bernard L.; Gobdel, Bruce C. (Academy of Management Journal, 1975)
Conflicting trends in the literature concerning task environments and structures conducive to creativity are reviewed, and an experiment examines the effects on creative performance of objectives, creativity procedures, and imposed control reports. Objectives specifying creativity and the imposition of control reports are found to enhance and inhibit creative performance respectively.